Strategi Pengambilan Keputusan dalam Penerimaan Peserta Didik Baru di SMP Negeri 57 Palembang (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze decision-making strategies in the implementation of the New Student Admission (PPDB) process at SMP Negeri 57 Palembang. This research is qualitative in nature, using a phenomenological approach. Data collection techniques include interviews, observations, and documentation. The research informants consist of the principal, the PPDB committee, and other parties involved in the PPDB implementation process. The data analysis technique is conducted through the stages of data reduction, data display, and conclusion drawing, while data validity is tested through source, method, and time triangulation. The results of the study indicate that decision-making strategies in the implementation of PPDB are carried out through systematic planning by considering government policies, school capacity, and actual conditions in the field. The decision-making process is implemented in a planned and data-driven manner through coordination between the principal and the PPDB committee, thereby maintaining the principles of objectivity, transparency, and accountability. However, the implementation of PPDB still faces several challenges, such as technical disruptions in the online registration system and limitations in human resources. Therefore, it is necessary to improve system management and strengthen coordination among committee members to ensure that the PPDB implementation can run more effectively and optimally.